Outcome of parathyroidectomy patients with secondary hyperparathyroidism - WANG Kang; WANG Xiang-yang; LI Yong-quan; LI Ya; ZHANG Xin-zhou (Linchuang shenzangbing zazhi)
Objective To study the outcome of total parathyroidectomy(PTX) and subtotal PTX in maintenance dialysis patients with secondary hyperparathyroidism.Methods Eighty-eight maintenance dialysis patients who underwent total PTX or subtotal PTX were followed up between Jun,2009 and Dec.2012.Blood samples were collected from the patients.Electro-chemiluminescence immunoassay was used to determine intra-operative iPTH level.According to iPTH level,total PTX or subtotal PTX was performed.Eighty-eight patients were divided into subtotal PHX group and total PHX group.The recurrence rate and outcomes were compared between the two groups.All the patients were also divided into no recurrence group and recurrence group according to the relapse and iPTH level.Log-rank tests were used to compare the recurrence rate of secondary hyperparathyroidism after the surgical procedures.The influencing factors of recurrence after parathyroidectomy were assessed.Results The follow-up time was 21 ± 11.3 months.The iPTH levels on the postoperative day 1 were higher in recurrence group than in no-recurrence group.During the follow-up period,10 and 1 cases relapsed respectively in the subtotal PTX group and total PTX group.There was no significant difference in survival curve between subtotal PTX group and total PTX group by log-rank test At 12,26 and 36 months,the cumulative recurrence rate in all 88 patients was 98.8%,91.3%and67.1%> respectively.Conclusions There was no significant difference in relapse rate between total PTX and subtotal PTX in maintenance dialysis patients with secondary hyperparathyroidism during a follow-up period of 1-4 years.After surgery the patient’s symptoms were significantly alleviated.The iPTH levels on the postoperative day 1 may be associated with the recurrence.